Seroprevalence of Toxoplasma Gondii in Parkinson’s Disease Iraqi Patients - Merdaw, Maysoon Abdul zahra; Kasim, Ali Abdulhussain; Salih, Mahmood Kahtan (Iraqi Journal of Pharmaceutical Sciences, 2021)
Background Several studies have addressed the prevalence of Toxoplasma gondii (T. gondii), among Parkinson’s disease (PD) patients in different countries, and the potential association between the infection and PD; the results of these studies were conflicting. The study aims to investigate the prevalence of Toxoplasma infection among sample of Iraqi PD patients. Also, to examine the potential association of age, PD duration, gender, smoking habit, zone of residence and family history of PD, with the prevalence of Toxoplasma infection in PD patients.Patients and Methods Seventy-four PD patients attaining Dr. Saad Al-Witry Neuroscience Hospital in Baghdad/ Iraq for routine follow up, from different Iraqi governorates, were enrolled in this cross-sectional study. Detection of T. gondii was performed by detection of anti-Toxoplasma IgG and IgM antibodies in serum by ELISA method.Results The frequency rate of anti-Toxoplasma IgG antibodies in Iraqi PD patients was 43.2% (32/74); while, none of the participants was seropositive for anti-Toxoplasma IgM antibody. Age, PD duration, smoking habit and zone of residences were not shown to be risk factors for Toxoplasma infection in PD patients (P>0.05); meanwhile, female gender and positive family history of PD were shown to have a protective effect ((OR, 0.309; 95% CI, 0.099-0.966; P= 0.043) and (OR, 0.162; 95% CI, 0.037-0.705; P=0.015); respectively).ConclusionsThe prevalence rate of Toxoplasma infection in Iraqi PD patients is 43.2%, female gender and positive family history of PD might protect against Toxoplasma infection in PD patients.Key words: Iraq, Neurodegeneration, Parkinson’s disease, Prevalence, Toxoplasma gondii